Arachidonic Acid Is a Safe and Efficacious Schistosomicide, and an Endoschistosomicide in Natural and Experimental Infections, and Cysteine Peptidase Vaccinated Hosts - Tallima, Hatem; Hanna, Violette S.; El Ridi, Rashika (Frontiers in Immunology, 2020)
Blood flukes of the genus Schistosoma are covered by a protective heptalaminated, double lipid bilayer surface membrane. Large amounts of sphingomyelin (SM) in the outer leaflet form with surrounding water molecules a tight hydrogen bond barrier, which allows entry of nutrients and prevents access of host immune effectors. Excessive hydrolysis of SM to phosphoryl choline and ceramide via activation of the parasite tegument-associated neutral sphingomyelinase (nSMase) with the polyunsaturated fatty acid, arachidonic acid (ARA) leads to parasite death, via allowing exposure of apical membrane antigens to antibody-dependent cell-mediated cytotoxicity (ADCC), and accumulation of the pro-apoptotic ceramide. Surface membrane nSMase represents, thus, a worm Achilles heel, and ARA a valid schistosomicide. Several experiments conducted in vitro using larval, juvenile, and adult Schistosoma mansoni and Schistosoma haematobium documented ARA schistosomicidal action. Arachidonic acid schistosomicidal action was shown to be safe and efficacious in mice and hamsters infected with S. mansoni and S. haematobium, respectively, and in children with light S. mansoni infection. A combination of praziquantel and ARA led to outstanding cure rates in children with heavy S. mansoni infection. Additionally, ample evidence was obtained for the powerful ARA ovocidal potential in vivo and in vitro against S. mansoni and S. haematobium liver and intestine eggs. Studies documented ARA as a potential endogenous schistosomicide in the final mammalian and intermediate snail hosts, and in mice and hamsters, immunized with the cysteine peptidase-based vaccine. These findings together support our advocating the nutrient ARA as the safe and efficacious schistosomicide of the future.